2017
DOI: 10.1177/1420326x17707564
|View full text |Cite
|
Sign up to set email alerts
|

Cooling energy reduction effect of parallel double-window system operation in residential buildings in South Korea

Abstract: This paper aims to derive the operational modes of a parallel double-window system that reduces cooling energy consumption and satisfies indoor comfort through natural ventilation. The parallel double-window system examined in this paper is a window system that could control indoor draft distribution and adjust the size of the opening depending on indoor and outdoor conditions. The system can be used in five ways (all close, out-open + in close, out-open+in open (tilt), out-open+in open (turn) and all open). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our findings show that the kind of natural ventilation has a significant impact on overheating intensity or cooling demand for both Korean and German apartment buildings. These findings are confirmed by Lee et al (2017) obtaining that natural ventilation for a residential building in Incheon, South Korea, can reduce the cooling energy demand by 60% in comparison unventilated once. For another German multi-residential building, we demonstrated that the realistic reproduction of window ventilation behaviour is vital to calibrate BPS models to monitored room temperature and its significant impact on overheating [64].…”
Section: Interdependence Of Building Design and Climate Conditions On...supporting
confidence: 61%
See 1 more Smart Citation
“…Our findings show that the kind of natural ventilation has a significant impact on overheating intensity or cooling demand for both Korean and German apartment buildings. These findings are confirmed by Lee et al (2017) obtaining that natural ventilation for a residential building in Incheon, South Korea, can reduce the cooling energy demand by 60% in comparison unventilated once. For another German multi-residential building, we demonstrated that the realistic reproduction of window ventilation behaviour is vital to calibrate BPS models to monitored room temperature and its significant impact on overheating [64].…”
Section: Interdependence Of Building Design and Climate Conditions On...supporting
confidence: 61%
“…However, in the last years a significant increase in studies focussing overheating evaluations could be obtained all around the globe, e.g. for China [25], in Sudanese [26], for Canada [27], for Honduras [28], for South Korea [29,30], for Austria [31,32], for Italy [33], for Sweden [34] or for Germany [35,36]. This trend highlights that overheating in residential buildings becomes an important global research topic, albeit the terminology of overheating is related to different comfort standards and climate conditions for different countries, cultures and climates.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical analysis for the evaluation of the thermal behavior of the abovementioned three samples was carried out through the commercial software package ANSYS v. 16© [51] by means of a 2-D simulation, in stationary state [52], because, according to previous studies, it was demonstrated that the 2-D analysis, using this software, accurately reproduces the behavior of the blocks, close to those obtained in a 3-D analysis for this specific type of polyhedral geometries [53,54].…”
Section: Building the Numerical Modelmentioning
confidence: 99%
“…The results revealed that natural ventilation can reduce more than 65% of the cooling degree hours. In another study, Lee et al (2019) evaluated the influence of a window with adjustable aperture size, using EnergyPlus. They concluded that employing natural ventilation can decrease cooling energy consumption by 60%.…”
Section: State Of Issuementioning
confidence: 99%